Overview of genomic and bioinformatic resources for Zymoseptoria. - Renwick, Alison; Oliver, Richard; Hane, James (Academic Press, 2015)
Zymoseptoria tritici (syn. Mycosphaerella graminicola, Septoria tritici) is a haploid fungus belonging to the class Dothideomycetes. It is the causal agent of septoria leaf blotch – one of the world’s most significant diseases of wheat. Here we review the genomic and bioinformatic resources that have been generated for Z. tritici. These include the whole-genome reference assembly for isolate IPO323, genome resequencing of alternate isolates, mitochondrial genome sequences, transcriptome sequences and expression data, and annotations of gene structure and function. We also highlight important advances in our fundamental knowledge of genome evolution and its effects on adaptation and pathogenicity in Z. tritici that have been facilitated by these resources.